Genetic and biochemical characterization of HMB-1, a novel subclass B1 metallo-β-lactamase found in a Pseudomonas aeruginosa clinical isolate. (8th January 2017) - Pfennigwerth, Niels; Lange, Felix; Belmar Campos, Cristina; Hentschke, Moritz; Gatermann, Sören G.; Kaase, Martin
Abstract : Objectives: To characterize a novel subclass B1 metallo-β-lactamase (MBL) found in an MDR Pseudomonas aeruginosa clinical isolate. Methods: The isolate P. aeruginosa NRZ-03096 was recovered in 2012 from an anal swab from a patient hospitalized in Northern Germany and showed high MICs of carbapenems. MBL production was analysed by several phenotypic tests. Genetic characterization of the novel bla gene and MLST was performed by WGS. The novel bla gene was expressed in Escherichia coli TOP10 and the enzyme was subjected to biochemical characterization to determine the kinetic parameters K m and k cat . Results: P. aeruginosa NRZ-03096 was resistant to all tested β-lactams and showed an MBL phenotype. Shotgun cloning experiments yielded a clone producing a novel subclass B1 enzyme with only 74.3% identity to the next nearest relative, KHM-1. The novel MBL was named HMB-1 (for Hamburg MBL). Analysis of WGS data showed that the bla HMB-1 gene was chromosomally located as part of a Tn 3 family transposon that was named Tn 6345 . Expression of bla HMB-1 in E. coli TOP10 led to increased resistance to β-lactams. Determination of K m and k cat revealed that HMB-1 had different hydrolytic characteristics compared with KHM-1, with lower hydrolytic rates for cephalosporins and a higher rate for imipenem. Conclusions: The identification of HMB-1 further underlines the ongoing spread and diversification of carbapenemases in Gram-negative human pathogens and especially in P. aeruginosa .